Rice husk/rice husk ash as an alternative source of silica in ceramics: A review - Hossain, SK S.; Mathur, Lakshya; Roy, P.K. (Journal of Asian Ceramic Societies, 2018)
Use of waste or by-products from different industries and the agricultural sector has received increasing attention in the scientific, technology, ecological, economic and social spheres in recent years. Rice husk (RH) is a by-product of rice milling and rice husk ash (RHA) is generated by combustion in a separate boiler. Both RH and RHA are abundantly accessible in rice growing countries such as China, India, Brazil, the USA, and Southeast Asia. RH has therefore been recycled by burning it for energy production. This generates RHA, which contains a huge quantity (85-95%) of amorphous silica. Over the past two decades, RHA has been used extensively in numerous fields for manufacturing of different silicates, zeolites, catalysts, nanocomposite, cement, lightweight construction materials, insulators, and adsorbents. This paper presents a comprehensive overview on the processing of nano-silica from RH/RHA. It tries at the same time, to present a critical review of the application of RHA as an ingredient for the production of various ceramic materials, e.g. refractory, glass, whiteware, oxide and non-oxide ceramics, silica aerogel and SiO 2 /C composites. In summary, amorphous silica derived from RHA or RH provides a potential alternative to conventional silica sources (e.g. quartz) for the manufacture of value-added ceramics for practical applications.